Design and analysis of a variable-stiffness robotic gripper - Daniel Cardin-Catalan (Elsevier, 2022)
This paper presents the design and analysis of a novel variable-stiffness robotic gripper, the RobInLab VS gripper. The purpose is to have a gripper that is strong and reliable as rigid grippers but adaptable as soft grippers. This is achieved by designing modular fingers that combine a jamming material core with an external structure, made with rigid and flexible materials. This allows the finger to softly adapt to object shapes when the capsule is not active, but becomes rigid when air suction is applied. A three-finger gripper prototype was built using this approach. Its validity and performance are evaluated using five experimental benchmark tests implemented exclusively to measure variable-stiffness grippers. To complete the analysis, our gripper is compared with an alternative gripper built by following a relevant state-of-the-art design. Our results suggest that our solution significantly outperforms previous approaches using similar variable stiffness designs, with a significantly higher grasping force, combining a good shape adaptability with a simpler and more robust design.